Pengaruh Literasi Keuangan dan Kepercayaan terhadap Minat Beli Produk Asuransi di Kalangan Mahasiswa - Ahmad Buchori; Nurhayati Nurhayati; Richy Wijaya W (Universitas Negeri Padang, 2022)
This study explains the relationship between research variables by testing existing hypotheses. In this study, the authors explain and examine the relationship between the independent variables in the form of financial literacy and perceptions of trust and the dependent variable is buying interest. This study is a quantitative study and questionnaires were collected and processed using variant-based Structural Equation Modeling (SEM).The results show that between the two variables, the perception of trust can act as the strongest predictor in predicting interest in buying insurance products among students. Then, the results also show that the level of student financial literacy can also predict the interest in buying insurance products among students quite well, although it is still lower than the influence of the variable perception of trust.